Effects of Paperless Trade Policy and Aid for Trade on Export Performance: Evidence from SASEC And CAREC Countries - Roy, Chandan Kumar; Xiaoling, Huang (Asian Development Policy Review, 2020)
The study aims to investigate the causal effect of cross-border paperless trade policy reforms and aid for trade on export performance in 14 Asian developing countries. Sample countries are selected based on membership of the South Asia Sub-regional and Economic Cooperation (SASEC) and Central Asia Regional Economic Cooperation (CAREC). This study uses annual panel data from 2005 to 2017, exploits the Economic and Social Commission for Asia and the Pacific (ESCAP) Trade Facilitation Measures survey data to sort out the pre-treatment and post-treatment period of the paperless trade policy transformation, and employs the difference-in-differences method of estimation. The results show that the adaptation of paperless trade facilitation policy measures and aid for trade to trade facilitation and the communication technology sector has a positive and statistically significant impact on export performance in Asian economies including in SASEC and CAREC region. However, the findings of this study also point out that the economic growth, foreign direct investment and the labour force has a positive effect on export performance. Thus the results from this study suggest that the export performance in these regions could be enhanced by adopting paperless trade policy measures and more aid allocation for the trade facilitation and communication technology sectors.